PROSES REGENERASI SIRIP EKOR PADA IKAN ZEBRA - Sari, Nila Kartika; Listyorini, Dwi; Gofur, Abdul (Program Studi Pendidikan Biologi, IKIP Budi Utomo Malang, 2016)
The caudal fin of Zebra fish as a model for studies regeneration both in terms of process and study of molecular analysis. This research is a descriptive exploratory. A sample of zebra fish (Danio rerio) 4-6 months of age as much as 30 individuals. The regeneration caudal fin of zebrafish observed by microscope with cutting vertically. The parameters observed were: 1) the time required for the regeneration process, 2) The regeneration process in details covering and, 3) Type of regeneration. Data in the form of the regeneration process ranging from wound healing to the original length obtained are collected in the form of digital photos. The results showed that the time required to regenerate the caudal fin to recover to normal at a temperature of 22-31° C was 22.25 ± 1.63 days for a model of vertical cuts. The regeneration process begins with the events of wound healing (H1) followed by the formation of blastema and will radius (H2) and continued differentiation characterized by the process of angiogenesis (H2). Regenerative development begins with the formation of the fingers and the growth of the peripheral areas tail fins faster than the medial region (H3-H8). End process regeneration in caudal fin of zebrafish are included in the development is the formation of regenerative segment radius starting from the proximal to the distal portion regenerat regenerat (H9 - ± H21). From the results of this research note that caudal fin of zebrafish to regenerate in epimorphosis.